Eficiência econômica da agropecuária nos municípios mineiros, 1996 e 2006, medida pela análise da fronteira estocástica (SFA) e pela análise envoltória de dados (DEA) - Loures, Alexandre Rodrigues (2013)
This dissertation evaluates economic efficiency level of Minas Gerais s farmers, at municipalities, in 1996 and 2006. This period is characterized for an increase technology through new equipment and agricultural research, by plant species in connection with physical chemical properties, as well. The methodologies were applied Data Envelopment Analysis DEA and Stochastic Frontier Analysis SFA, in 750 municipalities and 842 municipalities, for 1996 and 2006, separately. For the non-parametric method a Scale Constant Returns technology was useful, despite in the parametric technology a half-normal asymmetric and truncated distributions were adopted. In connection with our results, a censored regression, Tobit methodology, was functional for identifying variables that explain efficiency ranks across municipalities. The major part of municipalities, in both measures, develops an efficiency level between 0.50 and 0.70, in a scale until 1.0. Only in half-normal error distributuion in SFA, for the 2006 year, the efficiency level was worst and observation distribution was below 0.50. In the SFA analysis any municipality was totally efficient despite two municipalities in DEA analysis becomes totally efficient. In relationship with efficiency level, a Tobit exercise demonstrates that fertilizers, soils chemicals and average of study yeares are statistically significant and, in consequence, contributes to better efficiency levels. In oppose indication, irrigation and soil rotation were variables that produces worst results for efficiencies levels. The results indicates the obligation to have a private and public policies, that encourage the adoption of new techniques by farmers, that would be resulting in improvement of efficiency levels.